भर्तृहरि र शतकत्रयम् - Poudel, Ram Chandra (Janabhawana Research Journal, 2025)
This article begins with an introduction to the subject matter. It then explains various aspects of the life of the author of the Shatakatraya, presenting the theoretical foundations of biographical criticism and the etymology of the word ‘biography.’ In this line, the lexical meaning of biography, its related definitions, and their conclusion are presented. Similarly, the article describes the poetic style of Bhartrihari and the foundational themes developed in Shatakatraya. The article concludes by outlining the achievements of all three shatakas.